Performance Process of Coil Winding Machine Based on Accuracy and Speed for Water Pump Motor - Ilahi, Novita Asma; Musyafiq, Afrizal Abdi; Purwiyanto; Rahmat, Saepul; Prima Dewi, Riyani; Purnata, Hendi (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
A coil winding machine for water pumps using a monitoring system is a development of conventional winding tools. In regular coil winding tools, the coil winding process is done manually by rotating the handle as many times as the desired number of turns. The conventional winding tools have problems consisting of inconsistent working speed and operator-dependent winding continuity. Undesirable windings can occur with conventional winding tools, and the winding process requires close supervision. Therefore, the automatic coil winding machine was developed to optimize the coil winding process. The machine utilizes a DC motor to rotate the coil rolls, replacing the conventional roller handle function. This machining method uses an optocoupler sensor. The sensor serves to identify and evaluate the rotation of the roller. In addition, the ATmega8 microcontroller was applied to develop a system that can work automatically. Data collection involves varying the number of wire turns and the wire diameter dimension. The variation is necessary because the number of windings and wire diameter affect pump efficiency and performance. The data testing showed a machine accuracy rate of 98%, with a maximum difference of 1 coil winding in the results. This data confirms that the coil winding machine meets the tool's accuracy standards.